Impact of mobile phones and internet use on financial inclusion: empirical evidence from the EU post-communist countries - Bayar, Yilmaz; Gavriletea, Marius Dan; Păun, Dragoş (Technological and Economic Development of Economy, 2021)
Poverty alleviation has become one of the biggest challenges for many countries and access to financial services is considered to be a key driver of development and economic growth. Finding solutions that can break down barriers that poor people are facing to access formal financial services has become a major concern for researchers, governments, financial institutions. Financial services must reinvent themselves and the adoption of new technology is a crucial key to overhaul their operations and to find innovative solutions to manage customer expectations. The escalation in access and penetration level of mobile phones and the Internet can improve financial inclusion by facilitating easy access to financial services, by providing secure transaction platforms, by reducing transaction costs, by providing a competitive business framework. There has been relatively limited research on the impact of Internet and mobile phones use on financial inclusion, therefore our main purpose was to investigate this linkage in a sample of 11 post-communist countries of the European Union from 1996–2017 using panel cointegration and causality analyses. Firstly, we investigated whether mobile cellular phone subscriptions and the rate of Internet usage affect financial institutions’ access; secondly, we analysed the impact of these variables on financial market access. Results indicate that mobile cellular phone subscriptions positively affect both financial institution access in countries like Hungary, Latvia, Lithuania, Poland, and Slovenia and financial market access in Bulgaria, Croatia, and Hungary. Also, a negative relationship between mobile cellular phone subscriptions and financial institution access was noticed in the Czech Republic and regarding financial market access in the Czech Republic and Poland. Our findings also indicate both positive and negative relationships between Internet usage rates and financial institutions and financial markets access. By increasing Internet usage we can improve access to financial institutions in Bulgaria, Croatia, Czech Republic, Hungary, and Poland and we can increase financial markets access in Latvia and Slovenia. First published online 13 April 2021